Community Self-Organisation in Neighbourhood Parks in Perumnas Mojosongo, Surakarta - Fajri, Muhammad Nur; Pradoto, Wisnu (Universitas Diponegoro, Indonesia, 2023)
This research examines the involvement of the community in creating and managing neighbourhood parks in Perumnas Mojosongo residential area, Surakarta, Indonesia, with the risk of transgression. The neighbourhood parks were undeveloped until residents intervened in these government land without legal permission. This research aims to explore the motives for intervening in these sites and the processes that drive the success of self-organised actions by local residents. It expands on previous studies by examining a different setting: spaces intended for public facilities in a planned residential area. The research began with a quantitative strand to select two sites that function properly as neighbourhood parks as the cases. The selection phase analysed the characteristics of the neighbourhood parks using frequency statistics by assessing the sites' condition from participant observation and official documents. Then, a multiple case study utilised semi-structured interviews to retrieve experiences from 16 key informants, residents with first-hand experiences regarding both parks’ development. The research concludes that residents' proximity to government-owned land motivates them to initiate park development, even on a small scale, when the government neglects the land. However, the legitimacy of their actions is only quasi-legitimate, as they lack formal permission from the government to utilise the land. Instead, their actions are supported by verbal permission, the perception of dispute resolution as a permit, or even the assumption of government funding as a form of approval. Social recognition from neighbourhood associations becomes a determinant of the safety of their actions.